Hydrophobic Solid Photothermal Slippery Surfaces with Rapid Self-repairing, Dual Anti-icing/Deicing, and Excellent Stability Based on Paraffin and Etching - Wei, Jue (Langmuir : the ACS journal of surfaces and colloids, 2024)
Ice and snow disasters have greatly affected both the global economy and human life, and the search for efficient and stable anti-icing/deicing coatings has become the main goal of much research. Currently, the development and application of anti-icing/deicing coatings are severely limited due to their complex preparation, structural fragility, and low stability. This work presents a method for preparing hydrophobic solid photothermal slippery surfaces (SPSS) that exhibit rapid self-repairing, dual anti-icing/deicing properties, and remarkable stability. A photothermal layer of copper oxide (CuO) was prepared by using chemical deposition and etching techniques. The layer was then impregnated with stearic acid and solid paraffin wax to create a hydrophobic solid photothermal slippery surface. This solves the issue of low stability on superhydrophobic surfaces caused by fragile and irretrievable micro/nanostructures. In addition, the underlying photothermal superhydrophobic surface provides good anti-icing/deicing properties even if the paraffin on the surface evaporates or is lost during operation. The findings indicate that when subjected to simulated light irradiation, the coating's surface temperature increases to 80 °C within 12 min. The self-repair process is completed rapidly in 170 s, and at -15 °C, it takes only 201 s for the ice on the surface to melt completely. The surface underneath the paraffin exhibited good superhydrophobic properties, with a contact angle (CA) of 154.1° and a sliding angle (SA) of 6.8° after the loss of paraffin. Simultaneously, the surface's mechanical stability and durability, along with its self-cleaning and antifouling properties, enhance its service life. These characteristics provide promising opportunities for practical applications that require long-term anti-icing/deicing surfaces